Sanctifying misandry : goddess ideology and the Fall of Man - Young, Katherine K., 1944-; Nathanson, Paul, 1947- (Montreal [Que.] : McGill-Queen's University Press, 2010)
In Sanctifying Misandry, Katherine Young and Paul Nathanson challenge an influential version of modern goddess religion, one that undermines sexual equality and promotes hatred in the form of misandry - the sexist counterpart of misogyny.
Prologue, the fall of man -- Introduction, pop goes the goddess -- From goddesses to witches (and back) : rewriting the Bible. Paradise lost : a golden age for women ; The fall of man : a dark age for women ; Paradise regained : a new golden age for women -- From reform to revolution : restoring the goddess. The green goddess : feminism for a therapeutic age ; History, herstory, or heresy : sophianity and the new reformation ; A hag for all seasons : the ultimate revolution ; Gynotopia : goddess ideology and misandry -- Epilogue : beyond the fall of man.
Includes bibliographical references and index.
Master record variable field(s) change: 082
Keywords: Goddess religion; Fall of man; Sin, Original; Sex role -- Religious aspects; Misandry; Goddess religion; Misandry; Sex role -- Religious aspects; Sin, Original; BODY, MIND & SPIRIT -- Spirituality -- Divine Mother, The Goddess, Quan Yin; SOCIAL SCIENCE -- Gender Studies; Fall of man; Goddess religion; Misandry; Sex role -- Religious aspects; Sin, Original; Electronic books